Graduate unemployment in Nigeria - Eshalomi, Matthew O. (Lagos, Nigeria : Eshalomi & Associates, 1983)
This book is the product of a post graduate research conducted by the author to critically analyse the genesis, structure and impact of graduate unemployment on the development of Abuja vis-a-avis other parts of Nigeria.
aia 28/05/13
Loan
Keywords: College graduates -- Employment -- Nigeria; Unemployed -- Nigeria; Unemployment -- Nigeria